High-energy-density all-solid-state lithium battery and preparation method thereof
By using the PPC-Peo-Litfsi interface layer in the full solid lithium battery, the problem of high solid lithium battery interface interface is solved, high energy density and security are achieved, and the battery charging efficiency and safety are improved.
Patent Information
- Application Number
- CN202411629716.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-01-28
AI Technical Summary
The interface impedance of solid-state lithium batteries is high, affecting ion transmission and battery energy utilization efficiency, and has safety risks such as liquid leakage, combustion and explosion.
The PPC-Peo-Litfsi is used as the interface layer to prevent the direct contact between the solid electrolyte and the lithium metal, and reduce the interface impedance through the PC wet interface between the PPC and lithium reaction product PC.
A large -capacity charging and discharge is achieved, the charging potential is reduced, the energy utilization efficiency is improved, and the safety of the battery is enhanced.
Smart Images

Figure CN119381533A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of solid-state lithium batteries, and in particular relates to a high-energy-density all-solid-state lithium battery and a preparation method thereof. Background Art
[0002] In recent years, among various commercial rechargeable / dischargeable chemical energy storage devices, lithium-ion batteries have the characteristics of high energy density and long service life. Since they were put on the market, they have attracted much attention and have been widely used in mobile phones, laptops, electric vehicles and other fields. However, with the development of electric vehicles and large-scale energy storage systems, people have put forward requirements for high energy density and high safety for chemical energy storage technology. At present, lithium-ion batteries use organic electrolytes. Due to the flammability of organic electrolytes and the narrow electrochemical stability window, traditional lithium-ion batteries not only have the disadvantage of insufficient theoretical energy density, but also have the safety risks of leakage, combustion and even explosion. Therefore, the use of solid electrolytes to replace organic electrolytes is expected to fundamentally solve the safety problems of all-solid-state batteries. As a key material for all-solid-state lithium batteries, solid electrolytes can effectively improve the safety and stability of batteries due to their high mechanical strength, excellent density and ability to resist the growth of lithium dendrites.
[0003] However, the interface problem between solid electrolytes and electrodes has greatly restricted the development of solid-state batteries. Due to the poor solid-solid interface contact between solid electrolytes and electrodes, the interface impedance of all-solid-state batteries is very large, which seriously affects the transmission of ions at the interface and reduces the battery's charge and discharge capacity and energy utilization efficiency.
[0004] In view of the above defects, the present application designs a high energy density all-solid-state lithium battery. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a high energy density all-solid-state lithium battery and a preparation method thereof. PPC-PEO-LiTFSI can be used to prevent direct contact between solid electrolyte materials and lithium metal, and the reaction product PC of PPC and lithium can effectively wet the interface and reduce the interface impedance. The high energy density all-solid-state lithium battery obtained by the present invention can achieve large-capacity charging and discharging, effectively reduce the charging overpotential, and improve the energy utilization efficiency.
[0006] To this end, the present invention provides a high energy density all-solid-state lithium battery, comprising: a lithium negative electrode, a solid electrolyte material, and an interface layer formed between the lithium negative electrode and the solid electrolyte material; the solid electrolyte material is Li 1+x Al x Ti 2-x (PO 4 ) 3, wherein 0.5>x>0.2; the interface layer is polypropylene carbonate-polyethylene oxide-composite bis(trifluoromethanesulfonyl)imide lithium PPC-PEO-LiTFSI.
[0007] Preferably, the thickness of the interface layer is 10-50 μm.
[0008] Preferably, the mass ratio of PPC, PEO and LiTFSI is (0.5-2):(10-15):(5-8).
[0009] The present invention also provides a method for preparing the high energy density all-solid-state lithium battery, comprising: (1) Preparation of Li 1+x Al x Ti 2-x (PO 4 ) 3 ; (2) Assembly of silver nanowires / Li 1+x Al x Ti 2-x (PO 4 ) 3 :The solid electrolyte material Li 1+x Al x Ti 2-x (PO 4 ) 3 After polishing, rinsing and drying, silver nanowire / dimethylacetamide solution was added to the surface, and silver nanowire / Li was obtained after drying. 1+x Al x Ti 2-x (PO 4 ) 3 ; (3) Preparation of PPC-PEO-LiTFSI: PPC, PEO and LiTFSI were dissolved in acetonitrile, stirred evenly by magnetic force, and then poured onto a glass plate with a polytetrafluoroethylene film. After drying, PPC-PEO-LiTFSI was obtained. (4) Assembling high energy density all-solid-state lithium battery: The positive electrode current collector is steel mesh, the negative electrode is lithium metal, and the silver nanowire / Li 1+x Al x Ti 2-x (PO 4 ) 3 / PPC-PEO-LiTFSI / Li are sequentially assembled and placed in an atmosphere-controlled chamber; after drying, the mixture is kept at 50°C-80°C for 1h-5h to obtain PPC-PEO-LiTFSI and Li 1+x Al x Ti 2-x (PO 4 )3 And the optimal contact between the lithium negative electrode; then oxygen is introduced into the cleaning control cavity, and oxygen is continuously introduced after cleaning, and a high energy density all-solid-state lithium battery is obtained after standing.
[0010] Preferably, the step (1) comprises: placing lithium hydroxide, aluminum oxide, titanium dioxide and ammonium dihydrogen phosphate in a ball mill for a first ball milling, followed by a first drying, grinding and a first calcining; further grinding the obtained product, adding a binder and anhydrous ethanol, and then performing a second ball milling, a second drying and grinding, and cold pressing to form a green embryo sheet; the green embryo sheet is subjected to a second calcination and polishing to obtain a high-density Li 1+x Al x Ti 2-x (PO 4 ) 3 .
[0011] Preferably, in step (1), lithium hydroxide, aluminum oxide, titanium dioxide and ammonium dihydrogen phosphate are weighed and reacted according to the stoichiometric ratio of Li:Al:Ti:P:O: (10-15): (1-5): (15-20): (20-40): (100-150), wherein the actual amount of lithium hydroxide used in the reaction is 110%-125% of the weighed amount.
[0012] Preferably, in the step (1), the first ball milling speed is 100-500 r / min, the first ball milling time is 5-20 h, wherein the forward rotation, reverse rotation and stationary time are the same, all 5-30 min, and the ball mass ratio is 1:2-1:8; the first drying temperature is 50-120°C; the first calcination is a step-by-step calcination, calcination at 300-550°C for 1-4 h, calcination at 600-950°C for 4-12 h, and the heating rate is 1-6°C / min; the binder is PVA (polyvinyl alcohol); the second ball milling speed is 100-500 r / min, the second ball milling time is 5-20 h; the second drying temperature is 50-120°C; the second calcination is a step-by-step calcination, calcination at 300-550°C for 1-4 h, calcination at 600-950°C for 4-12 h, and the heating rate is 1-6°C / min.
[0013] Preferably, in step (2), the polishing mesh size is 500-6000 mesh; the drying temperature is 50-120°C, and the drying time is 1-8h to obtain silver nanowires / Li 1+x Al x Ti 2-x (PO 4 ) 3 .
[0014] Preferably, in step (3), the mass ratio of PPC, PEO and LiTFSI is (0.5-2):(10-15):(5-8); the magnetic stirring time is 2-10 h; the drying temperature is 50-100° C., and the drying time is 5-20 h.
[0015] Preferably, in step (4), the mesh size of the steel wire mesh is 50-500 meshes; the drying temperature is 40-100°C, and the drying time is 1-5 hours; the oxygen cleaning time is 5-60 minutes; and the flow rate of oxygen continuously introduced after cleaning is one bubble per 2-3 seconds.
[0016] Compared with the prior art, the advantages and positive effects of the present invention are: (1) The present invention utilizes PPC-PEO-LiTFSI to prevent direct contact between solid electrolyte materials and lithium metal, and the reaction product PC of PPC and lithium can effectively wet the interface and reduce the interface impedance. The high energy density all-solid-state lithium battery obtained by the present invention can achieve large-capacity charging and discharging, effectively reduce the charging overpotential, and improve the energy utilization efficiency.
[0017] (2) The present invention uses silver nanowires as the positive electrode, which helps the conduction of lithium ions and electrons, promotes oxygen diffusion, and avoids the problem of traditional carbon-based materials being easily oxidized and causing side reactions to produce lithium carbonate.
[0018] (3) The present invention obtains a high-density solid electrolyte material, Li1+xAlxTi2-x(PO4)3, by cold pressing and sintering. It has high ionic conductivity and is air-stable without producing lithium carbonate. It also solves the safety problems caused by the volatility, leakage, oxidation, and lithium dendrites of traditional organic electrolytes, as well as the high cost disadvantage of aqueous electrolytes that must add a lithium isolation layer.
[0019] After reading the specific embodiments of the present invention in conjunction with the accompanying drawings, other features and advantages of the present invention will become more clear. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 Li prepared in Example 1 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 XRD pattern of Figure 2 Li prepared in Example 1 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 SEM images of Figure 3 The silver nanowire / Li prepared in Example 1 1.3 Al0.3 Ti 1.7 (PO 4 ) 3 XRD pattern of Figure 4 The silver nanowire / Li prepared in Example 1 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 SEM and EDS images; Figure 5 The cycle curve of the high energy density all-solid-state lithium battery prepared in Example 1; Figure 6 XRD diagram of the positive electrode product after cycling of the high energy density all-solid-state lithium battery prepared in Example 1; Figure 7 The SEM and EDS images of the positive electrode side products of the high energy density all-solid-state lithium battery prepared in Example 1 after cycling; Figure 8 Li prepared in Comparative Example 1 6.4 La 3 Zr 1.4 Ta 0.6 O 12 XRD pattern of Fig. 9 Li prepared in Comparative Example 1 6.4 La 3 Zr 1.4 Ta 0.6 O 12 SEM images of Fig.10 Silver nanowire / Li prepared in Comparative Example 1 6.4 La 3 Zr 1.4 Ta 0.6 O 12 XRD pattern of Fig.11 Silver nanowire / Li prepared in Comparative Example 1 6.4 La 3 Zr 1.4 Ta 0.6 O 12 SEM images of Fig.12 This is the cycle curve of the all-solid-state lithium battery prepared in Comparative Example 1. DETAILED DESCRIPTION
[0021] The present invention will be further described below in conjunction with specific embodiments. These embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. Meanwhile, after reading the present invention, those skilled in the art may make various modifications or changes to the present invention, and these equivalent forms also fall within the scope limited by the appended claims of the application.
[0022] The high energy density all-solid-state lithium battery of the present invention comprises a lithium negative electrode, a solid electrolyte material, and an interface layer formed between the lithium negative electrode and the solid electrolyte material; the solid electrolyte material is Li 1+x Al x Ti 2-x (PO 4 ) 3 , where 0.5>x>0.2; the interface layer is polypropylene carbonate-polyethylene oxide-composite bis(trifluoromethanesulfonyl)imide lithium PPC-PEO-LiTFSI.
[0023] The interface layer of the present application is polypropylene carbonate-polyethylene oxide-composite bis(trifluoromethanesulfonyl)imide lithium PPC-PEO-LiTFSI. The introduction of the interface layer can avoid direct contact between metallic lithium and solid electrolyte, effectively improve the interfacial wettability between metallic lithium and solid electrolyte, achieve closer interfacial contact between metallic lithium and solid electrolyte, reduce interfacial impedance, and prevent the occurrence of interfacial side reactions; thereby, the high energy density all-solid-state lithium battery obtained by the present invention can achieve large-capacity charging and discharging, effectively reduce charging overpotential, and improve energy utilization efficiency.
[0024] Polypropylene carbonate PPC can react with lithium negative electrode to generate polycarbonate PC, which can effectively improve the interfacial wettability between metallic lithium and solid electrolyte, achieve closer interfacial contact between metallic lithium and solid electrolyte, reduce interfacial impedance and prevent the occurrence of interfacial side reactions.
[0025] Since the surface of lithium metal contains alkaline components such as lithium hydroxide and / or lithium carbonate, when polypropylene carbonate PPC comes into contact with alkaline lithium, a chemical reaction occurs, causing the PPC molecular chain to break in the alkaline environment formed on the surface of lithium metal, generating small molecule carbonate PC. This process not only involves the breakage of carbonate groups in PPC molecules to release PC molecules, but also the continuous release of PC can improve the ionic conductivity and interfacial compatibility of solid polymer electrolytes, and help form a stable SEI (solid electrolyte interface) layer. PC molecules can penetrate into the polymer, reduce its crystallinity, improve ion transport performance, and promote the dissociation of bis(trifluoromethanesulfonyl)imide lithium salt LiTFSI, further enhancing ionic conductivity. In addition, the continuous release of PC also helps to form a LiF, Li-rich surface on the surface of lithium metal. 3 N and Li 2S and other components, which have excellent lithium ion conductivity and good wettability with lithium metal, thereby improving the interfacial stability and cycle performance of the battery.
[0026] Polyethylene oxide PEO composite bis(trifluoromethanesulfonyl)imide lithium LiTFSI can facilitate the transmission of lithium ions and electrons, promote oxygen diffusion, and improve the charging and discharging capacity of the battery.
[0027] The thickness of the interface layer is 10-50 μm, preferably, the thickness of the interface layer is 25-35 μm. The interface layer within this thickness range can effectively avoid direct contact between metal lithium and solid electrolyte, effectively improve the interfacial wettability between metal lithium and solid electrolyte, achieve closer interfacial contact between metal lithium and solid electrolyte, reduce interfacial impedance, and prevent the generation of interfacial side reactions; thus, the high energy density all-solid-state lithium battery obtained by the present invention can achieve large-capacity charging and discharging, effectively reduce charging overpotential, and improve energy utilization efficiency.
[0028] The mass ratio of PPC, PEO, and LiTFSI is (0.5-2): (10-15): (5-8), which can effectively avoid direct contact between metal lithium and solid electrolyte, effectively improve the interfacial wettability between metal lithium and solid electrolyte, achieve closer interfacial contact between metal lithium and solid electrolyte, reduce interfacial impedance, and prevent the occurrence of interfacial side reactions; thereby, the high energy density all-solid-state lithium battery obtained by the present invention can achieve large-capacity charging and discharging, effectively reduce charging overpotential, and improve energy utilization efficiency.
[0029] The present invention also provides a method for preparing the high energy density all-solid-state lithium battery, comprising: (1) Preparation of Li 1+x Al x Ti 2-x (PO 4 ) 3 : Lithium hydroxide, aluminum oxide, titanium dioxide and ammonium dihydrogen phosphate are placed in a ball mill for the first ball milling, followed by the first drying, grinding and the first calcination; the obtained product is further ground, and a binder and anhydrous ethanol are added, and then the product is subjected to the second ball milling, the second drying and grinding, and then cold pressed into a green embryo sheet; the green embryo sheet is subjected to the second calcination and polishing to obtain a high-density Li 1+x Al x Ti 2-x (PO 4 ) 3 .
[0030] In step (1), lithium hydroxide, aluminum oxide, titanium dioxide and ammonium dihydrogen phosphate are weighed and reacted according to the stoichiometric ratio of Li:Al:Ti:P:O (10-15):(1-5):(15-20):(20-40):(100-150), wherein the actual amount of lithium hydroxide used in the reaction is 110%-125% of the weighed amount.
[0031] The stoichiometric ratio of Li:Al:Ti:P:O is (10-15):(1-5):(15-20):(20-40):(100-150). Preferably, the stoichiometric ratio of Li:Al:Ti:P:O is 13:3:17:30:120. The reaction components are weighed according to the above stoichiometric ratio, so that the prepared solid electrolyte Li 1+x Al x Ti 2-x (PO 4 ) 3 The structure is stable, the structure is stable and orderly, the ion conductivity is high, and the air is stable without the generation of lithium carbonate; the solid electrolyte prepared in this application can solve the safety problems caused by the volatility, leakage, oxidation, lithium dendrites, etc. of traditional organic electrolytes, as well as the high cost disadvantage of the aqueous electrolyte that a lithium isolation layer must be added.
[0032] Since part of lithium hydroxide will be lost during the calcination process, the actual reaction amount of lithium hydroxide should be more than the weighed amount. The actual reaction amount of lithium hydroxide is 110%-125% of the weighed amount, which can make up for the loss of lithium hydroxide during the calcination process.
[0033] In step (1), the first ball milling speed is 100-500 r / min, the first ball milling time is 5-20 h, wherein the forward rotation, reverse rotation and stationary time are the same, all 5-30 min, and the ball mass ratio is 1:2-1:8; the first drying temperature is 50-120°C; the first calcination is a step-by-step calcination, which is calcined at 300-550°C for 1-4 h and calcined at 600-950°C for 4-12 h, and the heating rate is 1-6°C / min; the binder is PVA (polyvinyl alcohol); the second ball milling speed is 100-500 r / min, and the second ball milling time is 5-20 h; the second drying temperature is 50-120°C; the second calcination is a step-by-step calcination, which is calcined at 300-550°C for 1-4 h and calcined at 600-950°C for 4-12 h, and the heating rate is 1-6°C / min.
[0034] Through the above process parameters, the reaction components can be fully mixed and uniform, which is conducive to the full growth of crystals and the acquisition of a solid electrolyte with a stable and orderly structure. 1+x Al x Ti 2-x (PO 4) 3 The ionic conductivity is high and the air is stable without the generation of lithium carbonate; the solid electrolyte prepared in this application can solve the safety problems caused by the volatility, leakage, oxidation, lithium dendrites, etc. of traditional organic electrolytes, as well as the high cost disadvantage of the aqueous electrolyte that a lithium isolation layer must be added.
[0035] (2) Assembly of silver nanowires / Li 1+x Al x Ti 2-x (PO 4 ) 3 :The solid electrolyte material Li 1+x Al x Ti 2-x (PO 4 ) 3 After polishing, rinsing and drying, 50-100 μL of silver nanowire / dimethylacetamide solution was added to the surface and dried to obtain silver nanowire / Li 1+x Al x Ti 2-x (PO 4 ) 3 ; The present invention uses silver nanowires as the positive electrode, and assembles the silver nanowires and solid electrolyte materials into a silver nanowire / Li 1+x Al x Ti 2-x (PO 4 ) 3 The structure can help the conduction of lithium ions and electrons, promote oxygen diffusion, and avoid the problem of traditional carbon-based materials being easily oxidized and causing side reactions to produce lithium carbonate.
[0036] In step (2), the grinding mesh size is 500-6000 mesh; the drying temperature is 50-120° C., and the drying time is 1-8 hours.
[0037] (3) Preparation of PPC-PEO-LiTFSI: PPC, PEO and LiTFSI were dissolved in acetonitrile, stirred evenly by magnetic force, and then poured onto a glass plate with a polytetrafluoroethylene film. After drying, PPC-PEO-LiTFSI was obtained. In step (3), the magnetic stirring time is 2-10 hours; the drying temperature is 50-100° C., and the drying time is 5-20 hours.
[0038] In step (3), the PPC content is 2-5wt%, and the ratio of PEO to LiTFSI is 3:4-3:1.
[0039] In step (3), the ratio of the volume of acetonitrile to the total mass of PPC\PEO\LiTFSI is (5-10) ml:1 g, which can help PPC, PEO and LiTFSI to be fully and evenly dissolved in acetonitrile, and help PPC, PEO and LiTFSI to form a stable electrolyte membrane on a glass plate with a polytetrafluoroethylene film.
[0040] (4) Assembling high energy density all-solid-state lithium battery: The positive electrode current collector is steel mesh, the negative electrode is lithium metal, and the silver nanowire / Li 1+x Al x Ti 2-x (PO 4 ) 3 / PPC-PEO-LiTFSI / Li are sequentially assembled and placed in an atmosphere-controlled chamber; after drying, the mixture is kept at 50°C-80°C for 1h-5h to obtain PPC-PEO-LiTFSI and Li 1+x Al x Ti 2-x (PO 4 ) 3 And the optimal contact between the lithium negative electrode; then oxygen is introduced into the cleaning control cavity, and oxygen is continuously introduced after cleaning, and a high energy density all-solid-state lithium battery is obtained after standing.
[0041] In step (4), the mesh size of the steel wire mesh is 50-500 meshes; the drying temperature is 40-100°C, and the drying time is 1-5 hours; the oxygen cleaning time is 5-60 minutes; and the flow rate of continuous oxygen introduction after cleaning is one bubble per 2-3 seconds. Example
[0042] The method for preparing a high energy density all-solid-state lithium battery of this embodiment comprises the following steps: (1) Preparation of Li 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 According to the chemical formula Li:Al:Ti:P:O = 13:3:17:30:120, 0.70538g LiOH, 0.3058g Al 2 O 3 , 2.7166 g TiO 2 、6.9 g NH 4 H 2 PO 4The precursor was added to the ball mill in sequence, wherein the lithium hydroxide was in excess of 15% based on the stoichiometric ratio; the ball mill was performed at a speed of 200 r / min for 12 hours, wherein the forward rotation was 15 minutes, the reverse rotation was 15 minutes, and the static rotation was 15 minutes, and the material / ball mass ratio was 1:4. After being taken out, the precursor was placed in an oven at 80°C for drying; the dried precursor was placed in an agate mortar and ground for about 1 hour until there was no obvious block solid, the powder was placed in an alumina crucible, kept at 450°C for 2 hours, and kept at 850°C for 8 hours, and the heating rate was 3°C / min; the sintered material was placed in an agate mortar and ground for about 1 hour, and the block was ground into powder; a PVA binder of 1% by mass was added, anhydrous ethanol was added, and the ball mill was performed at a speed of 200 r / min for 12 hours. The ball-milled slurry was placed in an oven at 80°C for drying, and ground in an agate mortar for about 1 hour, and the ground powder was sieved through a 150-mesh screen; 0.2 g of LATP powder was cold pressed into green discs with a diameter of 12 mm. The LATP green discs were sintered by buried firing, kept at 450°C for 2 hours, kept at 900°C for 6 hours, and the heating rate was 3°C / min. The obtained ceramic electrolyte was recorded as LATP. Polishing treatment of the ceramic electrolyte surface: first polish with 800 mesh sandpaper, then polish with 2000 mesh sandpaper, and finally polish with 5000 mesh until the surface of the ceramic electrolyte is smooth; (2) Assembly of silver nanowires / Li 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 : The LATP ceramic electrolyte was polished with 800 mesh, 2000 mesh, and 5000 mesh sandpaper, rinsed with anhydrous ethanol, and dried in an oven at 80°C for 4 hours. 80 μL of AgNWs / DMF solution was added to the surface of the LATP ceramic electrolyte, and dried in an oven at 80°C for 24 hours to obtain the AgNWs / LATP cathode / electrolyte structure; (3) Preparation of PPC-PEO-LiTFSI: PEO was used as the raw material, PPC and lithium salt LiTFSI were added, and the solvent was acetonitrile. A PEO-based solid polymer electrolyte membrane was prepared by solution casting. The specific steps are as follows: 0.6g PEO, 0.4g LiTFSI and 0.05g PPC were dissolved in 6 ml acetonitrile, stirred for 6 hours with a magnetic stirrer to obtain a homogeneous solution. The mixed solution was then cast onto a glass plate with a polytetrafluoroethylene film, and dried at 60°C for 12 hours to remove the acetonitrile. The obtained electrolyte membrane PPC-PEO-LiTFSI was cut into electrolyte discs with a diameter of 12mm and a thickness of 30μm using a slicer; (4) Assembly of high energy density all-solid-state lithium battery: The assembly of AgNWs / LATP was completed in an argon glove box. The current collector was a 200 mesh steel wire mesh with a diameter of 12 mm, the negative electrode was a lithium metal with a diameter of 10 mm, and the LATP was physically isolated from the lithium metal negative electrode by a PPC-PEO-LiTFSI electrolyte membrane to avoid Ti 4+ Will be restored to Ti 3+ After assembly, it was placed in a self-made gas atmosphere control chamber. Before testing, the self-made gas atmosphere control chamber was placed in a 60°C oven for 3 h to soften PEO, so that the PPC-PEO-LiTFSI electrolyte membrane was fully in contact with the lithium metal anode and LATP, and then O was passed through the chamber for 20 min. 2 Clean the gas atmosphere control chamber, and continue to ventilate the chamber after cleaning. 2 The oxygen flow rate was controlled to be one bubble per 2-3 seconds. The battery was placed in a constant temperature room at 30°C for 5 hours before various tests were performed.
[0043] The preparation method of the all-solid-state lithium battery of this comparative example 1 comprises the following steps: (1) Preparation of Li 6.4 La 3 Zr 1.4 Ta 0.6 O 12 :According to the stoichiometric ratio of Li:La:Zr:Ta:O= 32:15:7:3:60, 1.8861g LiOH·H 2 O, 2.8487 g La(OH) 3 , 0.8625g ZrO 2 and 1.3257 g Ta 2 O 5 , where LiOH·H 2 O has an excess of 15 wt%; ball milling is performed at a speed of 250 rpm / s for 12 h, including 15 min of forward rotation, 15 min of reverse rotation, and 15 min of rest. The mass ratio of the material to the zirconium dioxide ball milling medium is 1:4, and the dispersant is anhydrous ethanol. The precursor slurry after ball milling is dried at 80 ° C to obtain a precursor powder, and the powder is placed in an agate mortar and ground until there is no obvious block solid, and then the powder is placed in ZrO 2 In a crucible, keep the temperature at 450℃ for 2h and 950℃ for 12h, with a heating rate of 3℃ / min; grind the sintered block solid in an agate mortar to powder, put 1g of LLZTO powder in a hot pressing mold, and hot press sinter at 1150℃ for 1h under argon atmosphere. The sintered LLZTO ceramic electrolyte is processed into a ceramic electrolyte with a diameter of 12±0.3mm and a thickness of 1±0.1mm; (2) Assembly of silver nanowires / Li6.4 La 3 Zr 1.4 Ta 0.6 O 12 : The LLZTO ceramic electrolyte was polished with 800 mesh, 2000 mesh, and 5000 mesh sandpaper, immersed in a 1 mol / L dilute hydrochloric acid solution for 10 seconds, rinsed with anhydrous ethanol, and dried in a vacuum oven for four hours. 80 μL of AgNWs / DMF was added to the surface of the LLZTO ceramic electrolyte, and dried in an oven at 80°C to obtain the AgNWs / LLZTO cathode / electrolyte structure; (3) Assembly of all-solid-state lithium battery: The assembly of AgNWs / LLZTO / Li all-solid-state lithium battery was completed in an argon glove box. After removing impurities on the surface of the lithium sheet, it was cut into 10 mm diameter discs with a sniper, attached to the LLZTO ceramic side of the AgNWs / LLZTO electrode / electrolyte structure, and pressed tightly. The assembled AgNWs / LLZTO / Li was placed on a 180°C heating table for 50 min, and then encapsulated in a Swage-lok type battery. A 200 mesh steel wire mesh with a diameter of 12 mm was placed on the AgNWs side as a current collector. After assembly, the Swage-lok was placed in a homemade gas atmosphere control chamber. Before testing, O was passed through for 20 min. 2 Clean the gas atmosphere control chamber, and continue to ventilate the chamber after cleaning. 2 The battery was placed in an oven at 80°C for 5 hours before various tests were performed.
[0044] Figure 1 Li prepared in Example 1 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 XRD pattern of Example 1 Li 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 The characteristic peaks correspond to Li 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 Standard PDF card 35-0754.
[0045] Figure 2 Li prepared in Example 1 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 SEM images of Figure 2 DisplayLi1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 The grains are in close contact with no gaps.
[0046] Figure 3 The silver nanowire / Li prepared in Example 1 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 XRD pattern of Figure 3 Silver nanowire / Li 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 The silver nanowires and LATP both correspond to the standard PDF card, indicating that there is no change after the electrode / electrolyte assembly, and the characteristic peaks of lithium carbonate do not appear at 21.5° and 23.4°.
[0047] Figure 4 The silver nanowire / Li prepared in Example 1 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 SEM and EDS images of Figure 4 It further shows that Ag nanowire / Li 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 The distribution is uniform, and EDS shows no C element, which once again confirms that no lithium carbonate is produced.
[0048] Figure 5 The cycle curve of the high energy density all-solid-state lithium battery prepared in Example 1 is: Figure 5 Demonstrated high energy density all-solid-state lithium battery can achieve 0.05mAh / cm 2 The constant capacity test shows that the first cycle charging platform is 3.25V, which is compared with the charging platform of non-aqueous lithium oxygen battery above 4V, indicating that the embodiment can realize large-capacity charging and discharging, and effectively reduce the charging overpotential and improve the energy utilization efficiency.
[0049] Figure 6 XRD diagram of the positive electrode product after cycling of the high energy density all-solid-state lithium battery prepared in Example 1; Figure 6 This indicates that after the cycle, in addition to the original electrode, the new substance produced is the regular product Li of the lithium oxygen battery. 2 O 2 , without producing lithium carbonate.
[0050] Figure 7 The SEM and EDS images of the positive electrode side products of the high energy density all-solid-state lithium battery prepared in Example 1 after cycling; Figure 7 This indicates that after the cycle, all elements correspond to the original substances and there is no C element, which once again confirms that no lithium carbonate is produced.
[0051] Figure 8 Li prepared in Comparative Example 1 6.4 La 3 Zr 1.4 Ta 0.6 O 12 XRD pattern of Li 6.4 La 3 Zr 1.4 Ta 0.6 O 12 All major peaks were consistent with standard PDF#45-0109.
[0052] Fig. 9 Li prepared in Comparative Example 1 6.4 La 3 Zr 1.4 Ta 0.6 O 12 SEM images of Fig. 9 Comparative Example Li 6.4 La 3 Zr 1.4 Ta 0.6 O 12 The grains are in close contact with no gaps.
[0053] Fig.10 Silver nanowire / Li prepared in Comparative Example 1 6.4 La 3 Zr 1.4 Ta 0.6 O 12 XRD pattern of Fig.10 Explanation of the constructed silver nanowire / Li 6.4 La 3 Zr 1.4 Ta 0.6 O 12 The characteristic peaks of lithium carbonate appear at 21.5° and 23.4°, which will affect the subsequent performance of the comparative example.
[0054] Fig.11 Silver nanowire / Li prepared in Comparative Example 1 6.4 La 3 Zr 1.4 Ta 0.6 O 12 SEM images of Fig.11 The existence of element C, namely the production of lithium carbonate, was further confirmed.
[0055] Fig.12 is the cycle curve of the all-solid-state lithium battery prepared in Comparative Example 1, Fig.12 The comparison all-solid-state lithium battery shows serious capacity decay from the second cycle and has poor cycle performance, which confirms the importance of lithium carbonate-free for the performance of all-solid-state lithium batteries.
[0056] In summary, through a comprehensive comparison between the embodiment and the comparative example, it can be seen that the present invention uses silver nanowires as the positive electrode, which is conducive to the conduction of lithium ions and electrons, promotes oxygen diffusion, and can avoid the problem of traditional carbon-based materials being easily oxidized to produce lithium carbonate by side reactions; the high-density solid electrolyte material obtained by cold pressing and sintering is Li 1+x Al x Ti 2-x (PO 4 ) 3 , high ion conductivity and air stability without lithium carbonate production, and solves the safety problems caused by the volatility, leakage, oxidation, lithium dendrites, etc. of traditional organic electrolytes, as well as the high cost disadvantage of adding a lithium isolation layer to aqueous electrolytes; PPC-PEO-LiTFSI is used to prevent direct contact between solid electrolyte materials and lithium metal, and the reaction product PC of PPC and lithium can effectively wet the interface and reduce the interface impedance. The high energy density all-solid-state lithium battery obtained by the present invention can achieve large-capacity charging and discharging, and effectively reduce the charging overpotential, thereby improving energy utilization efficiency.
[0057] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for a person skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to replace some of the technical features therein by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions claimed to be protected by the present invention.
Claims
1. A high energy density all-solid-state lithium battery, characterized in that: include: A lithium negative electrode, a solid electrolyte material, and an interface layer formed between the lithium negative electrode and the solid electrolyte material; The solid electrolyte material is Li 1+x Al x Ti 2-x (PO4)3, where 0.5>x>0.2; The interface layer is polypropylene carbonate-polyethylene oxide-composite bis(trifluoromethanesulfonyl)imide lithium PPC-PEO-LiTFSI.
2. The high energy density all-solid-state lithium battery according to claim 1, characterized in that: The thickness of the interface layer is 10-50 μm.
3. The high energy density all-solid-state lithium battery according to claim 1, characterized in that: The mass ratio of PPC, PEO and LiTFSI is (0.5-2):(10-15):(5-8).
4. The method for preparing a high energy density all-solid-state lithium battery according to any one of claims 1 to 3, characterized in that: include: (1) Preparation of Li 1+x Al x Ti 2-x (PO4)3; (2) Assembly of silver nanowires / Li 1+x Al x Ti 2-x (PO4)3: Solid electrolyte material Li 1+x Al x Ti 2-x (PO4)3 was polished, rinsed and dried, and silver nanowire / dimethylacetamide solution was added to its surface. After drying, silver nanowire / Li 1+ x Al x Ti 2-x (PO4)3; (3) Preparation of PPC-PEO-LiTFSI: PPC, PEO and LiTFSI were dissolved in acetonitrile, stirred evenly by magnetic force, and then poured onto a glass plate with a polytetrafluoroethylene film. After drying, PPC-PEO-LiTFSI was obtained. (4) Assembling high energy density all-solid-state lithium battery: The positive electrode current collector is steel wire mesh, the negative electrode is lithium metal, and the silver nanowire / Li 1+x Al x Ti 2-x (PO4)3 / PPC-PEO-LiTFSI / Li were sequentially assembled and placed in an atmosphere-controlled chamber; after drying, the mixture was kept at 50°C-80°C for 1h-5h to obtain PPC-PEO-LiTFSI and Li 1+x Al x Ti 2-x The optimal contact between (PO4)3 and the lithium negative electrode is achieved; oxygen is then introduced into the cleaning control chamber, and oxygen is continuously introduced after cleaning, and a high energy density all-solid-state lithium battery is obtained after standing.
5. The method for preparing a high energy density all-solid-state lithium battery according to claim 4, characterized in that: The step (1) comprises: placing lithium hydroxide, aluminum oxide, titanium dioxide and ammonium dihydrogen phosphate in a ball mill for a first ball milling, followed by a first drying, grinding and a first calcining; further grinding the obtained product, adding a binder and anhydrous ethanol, and then performing a second ball milling, a second drying and grinding, and cold pressing to form a green embryo sheet; the green embryo sheet is subjected to a second calcination and polishing to obtain a high-density Li 1+x Al x Ti 2-x (PO4)3.
6. The method for preparing a high energy density all-solid-state lithium battery according to claim 5, characterized in that: In the step (1), lithium hydroxide, aluminum oxide, titanium dioxide and ammonium dihydrogen phosphate are weighed and reacted according to the stoichiometric ratio of Li:Al:Ti:P:O (10-15):(1-5):(15-20):(20-40):(100-150), wherein the actual amount of lithium hydroxide used in the reaction is 110%-125% of the weighed amount.
7. The method for preparing a high energy density all-solid-state lithium battery according to claim 5, characterized in that: In the step (1), the first ball milling speed is 100-500 r / min, the first ball milling time is 5-20 h, wherein the forward rotation, reverse rotation and stationary time are the same, all 5-30 min, and the ball mass ratio is 1:2-1:8; The first drying temperature is 50-120°C; The first calcination is carried out in steps, calcining at 300-550°C for 1-4h, calcining at 600-950°C for 4-12h, and the heating rate is 1-6°C / min; The binder is PVA (polyvinyl alcohol); The second ball milling speed is 100-500r / min, the second ball milling time is 5-20h; the second drying temperature is 50-120℃; The second calcination is a step-by-step calcination, which is calcined at 300-550°C for 1-4h and 600-950°C for 4-12h, respectively, and the heating rate is 1-6°C / min.
8. The method for preparing a high energy density all-solid-state lithium battery according to claim 4, characterized in that: In the step (2), the polishing mesh size is 500-6000 mesh; the drying temperature is 50-120°C, and the drying time is 1-8h to obtain silver nanowires / Li 1+x Al x Ti 2-x (PO4)3.
9. The method for preparing a high energy density all-solid-state lithium battery according to claim 4, characterized in that: In the step (3), the mass ratio of PPC, PEO and LiTFSI is (0.5-2): (10-15): (5-8); The magnetic stirring time is 2-10h; the drying temperature is 50-100℃, and the drying time is 5-20h.
10. The method for preparing a high energy density all-solid-state lithium battery according to claim 4, characterized in that: In the step (4), the mesh size of the steel wire mesh is 50-500 meshes; the drying temperature is 40-100°C, and the drying time is 1-5 hours; the oxygen cleaning time is 5-60 minutes; and the flow rate of continuous oxygen introduction after cleaning is one bubble per 2-3 seconds.